Peran Strength-Based Parenting terhadap Subjective Well-Being pada Remaja Akhir Bersuku Sunda - Andrea, Revania; Sulastra, Marissa Chitra (Universitas Negeri Makassar, 2025)
The research was conducted to determine the role of strength-based parenting on subjective well-being (reviewed using three separate components: life satisfaction, positive affect, and negative affect) in Sundanese late adolescents. Parents can apply strength-based parenting by recognizing and encouraging Sundanese adolescents to use their strengths, so they can increase life satisfaction and positive affect, as well as reduce negative affect. This quantitative research was conducted on 202 Sundanese adolescents aged 18-21 years, with data processed using a correlational design with a simple linear regression analysis test. Data were collected online through the Strength-Based Parenting Scale (SBPS), Satisfaction with Life Scale (SWLS), and Scale of Positive and Negative Experience (SPANE) questionnaires, all of which were tested for validity and reliability. The research results show that strength-based parenting has a positive role in life satisfaction (R2 = 0.243; β = 0.493; p = 0.000) and positive affect (R2 = 0.159; β = 0.108; p = 0.000), as well as a negative role in negative affect (R2 = 0.046; β = -0.059; p = 0.002). Researchers hope that this research can serves as a useful reference for other researchers and help Sundanese parents implement strength-based parenting with Sundanese adolescents.